The semiotics of rhythm in the titles of Nazik al-Malaika's poems - الله, ژينو عبد; فؤاد, نيان نوشيروان (Sulaimani Journal for Humanities, 2019)
Although, Nazik al-Malaika is regarded as one of the pioneer of the Free-verse in Arabic poetry but, at the same time, her rhythmical poetic started from the early time of her writing poetry either in the level of inner or outer rhythms . The range using of this kind, comparing with her free –verse, is very limited.This is, maybe, because of her tying with the rules of classical methods of Arabic meter and rhyme. In this study named ; Rhythmical titles of Nazik al-Malaik, s poetry ; we ,first ,concentrate on the definitions of rhythm in general because its very common and natural using in poetry .It depends on regular and spontaneous systems of tone or melody such as a beating heart, of course, according to the psychological feelings of the poet .Then we concentrate on the relationship between music and rhythm, that’s because there are a great technical and emotional relationships between the two .Under the circumstances of this study we have to pay attention to the inner and outer rhythm in particular in poetical titles of Nazik al-Malaiks poetry. Here,we much concern on the inner rhythm. This is mainly because it contains a lot of dynamic voices inside words and phrases .All of this came by the semiological applications of Nazik al-Malaiks titles poems